Gestão e produtividade no centro cirúrgico com ênfase no giro de sala operatória - Morais, Letícia Nunes de (Brasil, 2022)
Objectives and Justification: The purpose of this study was to conduct a literature review, aiming to measure the importance of hospital management and its impact on professionals and patients, with emphasis on room turnover time. To demonstrate the relevance of optimizing room turnaround time for the service, as well as to evaluate strategies that can be used to optimize the dynamics between one surgery and another.